Online structure for political action - Schneider, Steven M. (Javnost (Ljubljana), 2002)
From the perspective of a citizen-Web user, what forms of political action might the presidential campaign sites in 2000 have catalyzed? This article explores the online structure - conceptualised as an electronic space within which an individual is given an opportunity to act -- for political action engendered by presidential campaign Web sites in the 2000 U.S. election. The Web sites of the thirteen presidential campaigns that were active in the 2000 American election are surveyed and analyzed. We find that the online structurefacilitated both online and offline political action, and illustrate several dimensions of this phenomenon.
Keywords: politične komunikacije; politični marketing; communication; komuniciranje; računalniške komunikacije; predvolilna kampanja; predsedniki; United States of America; ZDA